Florida's Bats: Florida Bonneted Bat - Holly K. Ober; Terry J. Doonan; Emily H. Evans (EDIS)
The Florida bonneted bat is one of only two endangered species of bat in Florida and the state’s only endemic flying mammal (“endemic” means that it is found nowhere in the world but in Florida). With a 20-inch wingspan, it is Florida’s largest bat and the third largest of all 48 species of bats in the United States. The Florida bonneted bat was listed as federally endangered in 2013 because of concerns over habitat loss, degradation, and modification caused by humans. Additional concerns include the species’ small population size and restricted range, the small number of known colonies, their slow reproduction, and the relative isolation of separate populations of bonneted bats. This 3-page fact sheet explains how to differentiate Florida bonneted bats from velvety free-tailed bats and Brazilian free-tailed bats and explains what to do if you find one of these endangered bats. Written by Holly K. Ober, Terry Doonan, and Emily Evans, and published by the UF Department of Wildlife Ecology and Conservation, October 2016.